The Use Of Images to Improve English Skills Including Listening, Reading, Speaking and Writing in Students - Lena, Maria Marta (BAHTRA: Pendidikan Bahasa dan Sastra, 2023)
The teaching and learning process is the main key to the success of the education system. Direct interaction between teachers and students is very essential to be prepared in an organized and structured manner. Apart from the national curriculum as a guide for making learning plans, developing learning components including teaching media is also important. This research aims to 1) find out whether visual media can improve the English vocabulary of students at SMP Negeri 4 Wolowaru. 2) Find out the extent of the effectiveness of learning in the classroom when teachers teach English using visual media. 3) Describe the advantages and disadvantages of using visual media in Class VII English learning at SMP Negeri 4 Wolowaru. This research is classroom action research applied to Class VII students at SMP Negeri 4 Wolowaru, which consists of 30 students. Before carrying out the research, the researcher gave a pre-test to find out the extent of the vocabulary possessed by the students. The pre-test results show that the average student score is 68.27. Meanwhile, the Minimum Completeness Criteria (MCC) for English is 75. After that, the researcher collaborated with the English teacher at SMP Negeri 4 Wolowaru to carry out cycle I using visual media. The average score of students after receiving visual teaching increased to 76.97. Thus, researchers still need to continue in cycle 2 to further optimize the increase in students' vocabulary acquisition using English visuals. In cycle 2, the researcher gave an evaluation of the vocabulary measurement test and the average score was 85.10. In explaining, teachers find it easy by using pictures. Apart from that, students are also very enthusiastic and active in the learning process. Based on observations, English learning activities become more interesting using pictures and drawings can also increase students' vocabulary.